2020
DOI: 10.30699/ajnmc.27.6.405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Education About Patient-controlled Analgesia Pump Preoperative on Severity of Pain, Nausea and Vomiting After Spinal Culumn Surgery

Abstract: Patients undergoing spinal column surgery, experience severe postoperative pain. One of the special methods of pain control is use of a patient-controlled analgesia (PCA) pump. Studies show that despite this pump, patients suffer from moderate to severe pain. Therefore, the teaching patients how to use the pump by nurses is essential. Therefore, the present study was conducted to determine the effect of patient education about patient-controlled analgesia pump preoperative on severity of pain, nausea and vomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…12 Similar to the present study, another randomized controlled trial was performed by Azizi et al in 2020 on the patients who underwent spinal and reported the parallel findings of enhanced patients' response to postoperative pain handling in that group who received pain-related education preoperatively than the control group. 13 A systematic review by Ramesh et al in 2017 also concluded that preoperative analgesia-related patient education lead to a decline in postoperative anxiety amongst cardiac patients who received the surgical intervention. 14 Another review stated that preoperative educational sittings catering to the medicinal, emotional, and monetary aspects with patients, who underwent spinal surgeries, undoubtedly reduced their depression/fear and improved their pain-related perception.…”
Section: Discussionmentioning
confidence: 99%
“…12 Similar to the present study, another randomized controlled trial was performed by Azizi et al in 2020 on the patients who underwent spinal and reported the parallel findings of enhanced patients' response to postoperative pain handling in that group who received pain-related education preoperatively than the control group. 13 A systematic review by Ramesh et al in 2017 also concluded that preoperative analgesia-related patient education lead to a decline in postoperative anxiety amongst cardiac patients who received the surgical intervention. 14 Another review stated that preoperative educational sittings catering to the medicinal, emotional, and monetary aspects with patients, who underwent spinal surgeries, undoubtedly reduced their depression/fear and improved their pain-related perception.…”
Section: Discussionmentioning
confidence: 99%